Er-Yag Laser Root Preparation During Subepithelial Connective Tissue Graft Procedures. - Ricardo Kina, José; Fumico Umeda Kina, Eunice; Kina, Juliana; Kina, Mônica (Journal of Dentistry And Oral Implants, 2019)
Areas of gingival recession cause either an esthetic problem and or root sensitivity. Obtaining predictable root coverage has become an important part of periodontal therapy. A deep, long – standing recession promoted by ANUG was treated using subepithelial connective tissue graft technique combined with decontamination of root surface by using Er:YAG laser. Our clinical findigs suggest that this technique is a predictable procedure to treat gingival recession and promote root decontamination.
Keywords: Laser Er-YAG; root surface; gingival recession; subepithelial connective tissue; gingival graft.